Pemanfaatan Sistem Informasi Database Online Perpustakaan Universitas Terbuka (UT) Sebagai Sumber Informasi - Adellia, Mayranda; Harahap, Mickael Halomoan; Harahap, Nursapia (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The title of this article is Utilization of the Open University Library's Online Database Information System as a Source of Information. This article aims to explain the reasons for the benefits of information systems in online databases in libraries and to find out about digital libraries. So it is important to utilize information sources easily, users can search for information more easily, users can search catalogs from outside the library. Leveraging information systems is not about automating some regularly performed tasks, but about creating new information flows that are integrated into a systematic integration system. However, there are still many problems in library management, including difficulty accessing the necessary information, lack of resources, and lack of effective and efficient management. When faced with these challenges, the use of databases is the best solution for libraries. Databases help libraries better manage and store information resources, making it easier for readers to access the information they need.